Ammonoid biostratigraphy of the Shannon Basin, western Ireland - Lacchia, Anthea R. (Trinity College (Dublin, Ireland). Department of Geology, 2016)
This study concerns ammonoid faunas from a classic turbidite succession, the Ross Sandstone Formation [Serpukhovian-Bashkirian) of the Shannon Basin, western Ireland. In addition to coastal exposures, a set of 12 behind-outcrop wells w e r e examined and sampled for biostratigraphy. More than 3,000 fossil specimens from the Clare Shale Formation and Ross Sandstone Formation were investigated. Given current lack of published information on the taxonomy of crushed ammonoid material, new systematic data on 14 Serpukhovian-Bashkirian ammonoids for which ontogenetic information was previously incomplete or lacking are presented. This information furthers knowledge of ammonoid ontogeny and also leads to more confident identification of ammonoids preserved as flattened external moulds. Marine fossils were commonly reported as confined to thin ammonoid-rich layers ("marine bands") bounded by barren strata, leading to a suggestion, based on examples from the Pennines, that fossil occurrence may be controlled by variations in salinity. While ammonoids are indeed concentrated in laterally extensive black shale bands, taken to represent intervals of sediment starvation, several new ammonoid-bearing horizons have been found in between the "marine bands" in the Shannon Basin, which are therefore better referred to as "condensed sections" or "ammonoid bands". The presence of ammonoids at various intervals outside the condensed sections is good evidence for normal marine salinity in the Ross Sands tone and associated Clare Shale Formation. The presence of normal marine faunas outside the traditional "marine bands" suggests that salinity values of the Shannon Basin and, by implication, other deep-water basins may well have been normal between periods of sediment starvation. Early biostratigraphic work in the basin recognized the presence of four ammonoid bands within the Ross Sandstone Formation. During the course of this study and in conjunction with research at University College Dublin, ten ammonoid-rich horizons [including eight condensed sections) have been identified within the Ross Sandstone. Faunal assemblages from the five main highly-condensed sections in the Ross Sandstone Formation are described in detail in this study, which is also the first to present details of abundance and pro portion of ammonoid taxa at localities within the Ross Sandstone Formation. These new biostratigraphic data, coupled with the lithostratigraphical correlations, provide the most detailed dataset for the Ross Sandstone Formation to date, also allowing biostratigraphy to be cross-checked against lithostratigraphical correlations. Overall, biostratigraphy was not as high-resolution as one might have hoped, in the sense that statistical analysis of the faunal assemblages does not always confirm that bands which are known to correlate by physical means are indeed indistinguishable. While some assemblages in condensed sections proved to be globally distinctive, most were not, and some were only locally distinctive; therefore most bands in the Ross Sandstone Formation cannot be confidently linked to a given ammonoid band in the Western European framework. This puts the validity of ammonoid-bearing condensed sections both in intrabasinal and extrabasinal correlation into question.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin